African swine fever vaccine: Turning a dream into reality. Issue 5 (29th June 2021) - Muñoz‐Pérez, Carolina; Jurado, Cristina; Sánchez‐Vizcaíno, José Manuel
Abstract: African swine fever (ASF) is currently threatening the swine industry at a global level. The disease originated in Africa has spread to Europe, Asia and Oceania, since 2007, reaching a pandemic dimension. Currently, the spread of ASF is unstoppable and that the development of a safe and effective vaccine is urgently required. The objective of this paper is to review the vaccine candidates tested during the 20th and 21st centuries, to identify the strengths and weaknesses of these studies and to highlight what we should learn. Several strategies have been explored to date, some of which have shown positive and negative results. Inactivated preparations and subunit vaccines are not a viable option. The most promising strategy would appear to be live attenuated vaccines, because these vaccine candidates are able to induce variable percentages of protection against certain homologous and heterologous virus isolates. The number of studies on live attenuated vaccine candidates has steadily increased in the 21st century thanks to advances in molecular biology and an in‐depth knowledge of ASF virus, which have allowed the development of vaccines based on deletion mutants. The deletion of virulence‐related genes has proved to be a useful tool for attenuation, although attenuation does not always mean protection and even less, cross protection. Therefore, ASF vaccine development has proved to be one of the top priorities in ASF research. Efforts are still being made to fill the gaps in the knowledge regarding immune response, safety and cross protection, and these efforts will hopefully help to find a safe and effective vaccine that could be commercialised soon, thus making it possible to turn a dream into reality.